Identity theft and university students: Do they know, do they care?. Issue 4 (29th August 2014) - Seda, Ludek
Abstract : Purpose: This study explains what factors influence the relationship between the university students' knowledge of the risk of identity theft and the preventive measures they take. Design/methodology/approach: A series of semi-structured interviews was used as the primary data-collection tool. The sample for this study comprised twelve undergraduate students (six males and six females) from the Flinders Business School. The interviews were designed as face-to-face interviews. Findings: The current findings indicate that, despite the fact that students were reasonably knowledgeable regarding the general risk of identity theft, many of the students had only limited knowledge about specific issues related to identity theft. It was found that the limited knowledge or misunderstanding of specific issues prevented students from using appropriate measures that could reduce the risk of identity theft. The students demonstrated a significant misunderstanding of who perpetrators typically were targeting when stealing personal information or what perpetrators of identity theft were looking for. Originality/value: The results of the study contribute to a better understanding of the students' knowledge about the risks associated with identity crime. They may also assist governments and other stakeholders with vested interests, such as financial institutions and educational providers, to educate individuals about the circumstances where they are potentially vulnerable to identity theft.